(untitled) (Strathmore Law Review, 2021)
The teaching of Public International Law (PIL) in African law schools is backward. While Article 13 of the International Covenant on Economic, Social and Cultural Rights demands that, for education to be acceptable, it must also be culturally appropriate, the teaching of PIL in our schools is largely only reflective of European westernisation. This study reviews relevant literature in law, sociology, international relations, history and politics, and rely on surveys on PIL syllabi in select leading African law schools to attempt to make this violation more explicit. As a recommendation of a possible way forward, the study provides PIL as taught in the Hut at Strathmore Law School. The Hut is an intellectual movement within Strathmore Law School that has tried to contextualise Third World Approaches to International Law (TWAIL) to Africa.